2019
DOI: 10.1186/s12909-019-1879-1
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide cross-sectional survey of student experiential practice at community pharmacies in South Korea

Abstract: BackgroundIn South Korea, community pharmacy experiential practice (CPEP) is very important because most pharmacists (71.8%) work in community pharmacies, which also employ the majority of students after graduation. The present study investigated student responses to the current CPEP status, suggestions for improvement, and advancement in their competency after practice based on evaluation of Community Pharmacy Experiential Practice Model (CPEPM) outcomes.MethodsA nationwide cross-sectional, self-administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…In a study conducted in South Korea in 2019 that examined students' experiential practice at community pharmacies, only a small percentage of students claimed that the knowledge they learned in school could be applied in the real world. This was similar to the finding of the current study (Kim et al, 2019). It seems that educational institutions should have the necessary tools to ensure that students are wellprepared for the career path and apply their knowledge in practice.…”
Section: Al-jalehawi Et Alsupporting
confidence: 90%
See 2 more Smart Citations
“…In a study conducted in South Korea in 2019 that examined students' experiential practice at community pharmacies, only a small percentage of students claimed that the knowledge they learned in school could be applied in the real world. This was similar to the finding of the current study (Kim et al, 2019). It seems that educational institutions should have the necessary tools to ensure that students are wellprepared for the career path and apply their knowledge in practice.…”
Section: Al-jalehawi Et Alsupporting
confidence: 90%
“…The inadequate time devoted to the training to get the desired benefits and information was reported as one of the main challenges for nearly half of the students. This was comparable with the study of Kim and researchers in which less than half of students claimed that there was a lack of educational training time (Kim et al, 2019). The reason for this may attributed to the time when this study was conducted, which was during the COVID-19 pandemic, where lockdown and local restrictions were in place, which limited the working hours of community pharmacies.…”
Section: Al-jalehawi Et Alsupporting
confidence: 85%
See 1 more Smart Citation
“…Veterans who responded “Sometimes”, “Often”, or “Always” were categorized as having experienced transportation barriers, while those that selected “Never” were classified as having no transportation barriers [ 11 ]. Consistent with prior studies that have assessed transportation barriers [ 11 ] and cross-sectional surveys [ 23 25 ], Veterans who did not respond or reported “Don’t know” were excluded from analysis ( n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…17 This is in agreement with results of research done on student in South Korea which emphasized the importance of community pharmacy as a site of training. 18 Results in Figure 4; B showed that around half of the participants (51%) agreed that quality of the educational program improved after certification and 27% disagreed. As for the quality of basic science and clinical instruction, 40.5% agreed that it was improved.…”
Section: Resultsmentioning
confidence: 94%